Functional approach to a Class II patient with upper first molar impaction - Giacomo D'Orlandi; Lorenzo Raguzzi; Efisio Defraia; Felicita Pierleoni (Wolters Kluwer Medknow Publications, 2014)
The lack of the left first molar maxillary and the left second molar maxillary, caused respectively by impaction and agenesis is a very rare case, which determines an important occlusal imbalance and asymmetrical mandible movement. A gnatologic and functional orthodontic approach were planned to improve the retrognathic mandible and the muscular activity using kinesiograph and electromyography.